PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN Bagian Kantor Pada PT. PLN(Persero) Area Pekanbaru Rayon Kota Timur - Nike Ningsih Purnama Sari; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine how the influence of organizational culture and work discipline on employee performance office section at PT.PLN (Persero) Area Pekanbaru Rayon City East.This research method is descriptive and quantitative by using program of SPSS 21,where sample used is employee part office PT.PLN (Persero) Area Pekanbaru Rayon City East with respondents as many 41 people. For sampling technique used census method. The Data collection techniques through questionnaires and interviews.The results of ananlisis use validity test, reability test, determination test, simple linear regression test, multiple linear regression test, t test and F test so that it can be seen that organizational culture variables significantly influence employee performance, that work discipline has a significant effect on employee performance, and A significant influence between organizational culture and work discipline on employee performance.keyword: Organizational Culture, Work Discipline, and Employee Performanc